THE IMPORTANCE OF THE ISSUE APPROACH IN THE DEVELOPMENT OF STUDENT MATHEMATICAL COMPETENCE - G. Akhmedova (Galaxy International Interdisciplinary Research Journal, 2023)
This article is about the importance of a problem approach in the development of mathematical competence of students. In particular, it is stated that the issue approach is a specially organized and systematically carried out training in the form of solving various educational problems.